Thermal analysis on a segmented thermoelectric generator. (1st February 2015) - Ming, T.; Wu, Y.; Peng, C.; Tao, Y.
Abstract: To improve their efficiency is of vital importance for the widespread application of TEG (thermoelectric generators). A design methodology, formulated on mathematical analysis and performed by spreadsheet calculation, was advanced to derive the optimum efficiency and geometrical dimensions of the STEG (segmented thermoelectric generator) module operating between 300 K and 780 K. The properties of the thermoelectric materials, such as the Seebeck coefficient, thermal conductivity, and electrical conductivity, were temperature-dependent. Meanwhile, a three-dimensional thermoelectric finite element model based on mathematical calculation was established to examine and verify the physical quantities when the STEG model operated in design condition. The simulation results indicated that this model is able to supply a steady voltage higher than 1.00 V and that the peak efficiency is about 11.2% when the load resistance is close to the internal resistance, which matches well with the mathematical analysis results. Furthermore, a series of tests were carried out to investigate the performance of an optimum TEG model under different conditions. It was found that the STEG can take full use of characteristics of different thermoelectric materials, and increase the efficiency and voltage output in most situations. Highlights: A mathematical model for the optimization of STEG (segmented thermoelectric generator) efficiency has been advanced. A thermodynamic model analyzing the TEG (thermoelectric generators) performance has been advanced. Non-uniform heat flux has significant effect on TEG performance. Transient heat flux has significant effect on TEG performance.